Bacterial cellulose adhesive composites for oral cavity applications. (15th November 2021) - Singh, Juhi; Tan, Nigel C.S.; Mahadevaswamy, Usha Rani; Chanchareonsook, Nattharee; Steele, Terry W.J.; Lim, Sierin
Abstract: Topical approaches to oral diseases require frequent dosing due to limited retention time. A mucoadhesive drug delivery platform with extended soft tissue adhesion capability of up to 7 days is proposed for on-site management of oral wound. Bacterial cellulose (BC) and photoactivated carbene-based bioadhesives (PDz) are combined to yield flexible film platform for interfacing soft tissues in dynamic, wet environments. Structure-activity relationships evaluate UV dose and hydration state with respect to adhesive strength on soft tissue mimics. The bioadhesive composite has an adhesion strength ranging from 7 to 17 kPa and duration exceeding 48 h in wet conditions under sustained shear forces, while other mucoadhesives based on hydrophilic macromolecules exhibit adhesion strength of 0.5–5 kPa and last only a few hours. The work highlights the first evaluation of BC composites for mucoadhesive treatments in the buccal cavity. Graphical abstract: Unlabelled Image Highlights: Bacterial cellulose (BC) physically modified into a light-activated bioadhesive Cellulose composites evaluated for adhesive properties to wet mucosal tissues Structure property evaluation-BC film type, joules light dose, hydration state Composites exhibited 2–5 times higher adhesion strength than existing formulations Composites achieved retention times of 2–7 days in harsh, dynamic environments